ICT-Based Teaching Materials for Reproductive System Learning in Senior High School - Tiarma Ayu Lestari Matondang; Hasruddin Hasruddin (Universitas Negeri Makassar, 2026)
Abstract Purpose: This study aimed to analyze the utilization of Information and Communication Technology (ICT)-based teaching materials in the learning and assessment processes of reproductive system material among senior high school students and to identify the challenges experienced by teachers and students during its implementation.Research Methodology: This study employed a qualitative descriptive approach conducted at SMA Negeri 12 Medan, Indonesia. The participants consisted of one biology teacher and 36 students of grade XI. Data were collected through classroom observations, questionnaires distributed via Google Forms, semi-structured interviews, and documentation. The teaching materials and digital platforms used in the learning process included animated videos from YouTube and the Quizizz application for assessment activities. Data were analyzed using thematic analysis through data reduction, categorization, interpretation, and conclusion drawing.Results: The findings revealed that ICT-based teaching materials positively supported biology learning by increasing students’ motivation, engagement, focus, and understanding of abstract reproductive system concepts. Animated videos helped visualize complex biological processes, while Quizizz created interactive and enjoyable assessment activities. However, several challenges were identified, including limited school facilities, inadequate student digital devices, unstable internet connections, and limited teacher creativity in developing innovative digital learning media.Conclusions: ICT-based teaching materials contribute positively to creating more interactive, engaging, and effective biology learning environments in senior high schools.Limitations: This study was limited to one school and used a qualitative descriptive design with a relatively small sample size.Contributions: This study contributes to biology education and digital learning research by providing insights into the implementation of ICT-based teaching materials to support 21st-century learning practices.Keywords: Teaching materials, information and communication technology, reproductive system